Characteristics and consequences of airway colonization by filamentous fungi in 201 adult patients with cystic fibrosis in France - Paugam, André; Baixench, Marie-Thérèse; Demazes-Dufeu, Nadine; Burgel, Pierre-Régis; Sauter, Elise; Kanaan, Reem; Dusser, Daniel; Dupouy-Camet, Jean; Hubert, Dominique (Medical mycology (Oxford), 2010)
A total of 657 sputum samples from 201 cystic fibrosis adult patients were collected during a 24-month period (2005-2006). We retrospectively analyzed the fungal colonization of the respiratory tract of these individuals by linking medical records and microbiological data. Filamentous fungi were isolated from specimens of 65.6% of the patients, with Aspergillus fumigatus being the predominant species recovered as it was found in specimens of 56.7% of the patients. We observed no difference for gender, pancreatic status and cirrhosis in patients with or without A. fumigatus colonization. We found a higher percentage of recovery of Pseudomonas aeruginosa, Stenotrophomonas maltophilia and nontuberculous mycobacteria in patients with A. fumigatus colonization. During the follow-up period of the study, 8.9% of the patients were diagnosed with allergic bronchopulmonary aspergillosis (ABPA). By a multivariate analysis we demonstrated that Scedosporium apiospermum was significantly associated with ABPA (Odds ratio = 13 [2-80]) as opposed to A. fumigatus (Odds ratio = 1.58 [0.49-5.05]).